Students’ mathematical reasoning ability in solving PISA-like mathematics problem COVID-19 context - Ismi Nurazizah; Zulkardi Zulkardi (Universitas Hamzanwadi, 2022)
This study aims to use the Pendidikan Matematika Realistik Indonesia (PMRI) approach to measure the mathematical reasoning ability of grade VII students in answering PISA-like mathematics problems on number content in the context of COVID-19. This study employs descriptive research with 34 participants from a junior high school in Palembang, Indonesia. Tests, interviews, and observations were utilized to collect data. The method of analysis adopted is descriptive. Google Meet is used to facilitate learning. Learning the PMRI technique was accomplished in this study by assigning sharing and jumping tasks. That is, assignments for students to discuss with each other have different levels of difficulty, followed by two exam questions. In the context of COVID-19, the test questions are PISA-like maths problems. The results show that students’ average mathematical reasoning skill is 63,037, with mathematical manipulation a common indicator. Most students have exhibited indications for presenting conjectures. However, only a few students have put down indicators for drawing logical conclusions, so drawing logical conclusions is an indicator that students rarely see. Overall, grade VII students' mathematical reasoning skills in answering PISA-like mathematics questions on number material in the context of COVID-19 utilizing the PMRI approach is good since students are used to modeling contextual problems such that mathematical manipulation indicators occur.